Spatial and temporal variations of greenhouse gas emissions from a waste stabilization pond: Effects of sludge distribution and accumulation. (1st April 2021) - Ho, Long; Jerves-Cobo, Ruben; Morales, Oscar; Larriva, Josue; Arevalo-Durazno, Maria; Barthel, Matti; Six, Johan; Bode, Samuel; Boeckx, Pascal; Goethals, Peter
Highlights: WSPs were strong sources of CO2 and CH4 and weak sinks of N2 O Spatial variation of GHG emission strongly depends on sludge distribution Diel variation was found in CO2 emissions but not in CH4 and N2 O emissions CO2 and N2 O dissolved concentrations can be used as a reference of their emissions Sludge management can be an important mitigation measure of carbon footprint in WSPs Abstract: Due to regular influx of organic matter and nutrients, waste stabilization ponds (WSPs) can release considerable quantities of greenhouse gases (GHGs). To investigate the spatiotemporal variations of GHG emissions from WSPs with a focus on the effects of sludge accumulation and distribution, we conducted a bathymetry survey and two sampling campaigns in Ucubamba WSP (Cuenca, Ecuador). The results indicated that spatial variation of GHG emissions was strongly dependent on sludge distribution. Thick sludge layers in aerated ponds and facultative ponds caused substantial CO2 and CH4 emissions which accounted for 21.3% and 78.7% of the total emissions from the plant. Conversely, the prevalence of anoxic conditions stimulated the N2 O consumption via complete denitrification leading to a net uptake from the atmosphere, i.e. up to 1.4±0.2 mg-N m −2 d −1 . Double emission rates of CO2 were found in the facultative and maturation ponds during the day compared to night-time emissions, indicating the important role of algal respiration, while no diel variation of the CH4 and N2 O emissions was found. Despite the uptake of N2 O, the total GHG emissions of the WSP was higher than constructed wetlands and conventional centralized wastewater treatment facilities. Hence, it is recommended that sludge management with proper desludging regulation should be included as an important mitigation measure to reduce the carbon footprint of pond treatment facilities.